2000
DOI: 10.1103/physrevb.61.7261
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly of the current self-oscillation frequency in the sequential tunneling of a doped GaAs/AlAs superlattice

Abstract: An anomalous behavior of the current self-oscillation frequency is observed in the dynamic dc voltage bands, emerging from each sawtoothlike branch of the current-voltage characteristic of a doped GaAs/AlAs superlattice in the transition process from static to dynamic electric field domain formations. Varying the applied dc voltage at a fixed temperature, we find that the frequency increases while the averaged current decreases. Inside each voltage band, the frequency has a strong voltage dependence in the tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…39 However, few papers focus on the voltage dependence of the oscillation period in the DVB region, except the works in Refs. 35,38,40, where the oscillation frequency was found to increase first and then decrease with increasing voltage. In the present work, we investigate the voltage dependence of the current oscillation period in the DVB region in a microscopic resonant tunneling model.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…39 However, few papers focus on the voltage dependence of the oscillation period in the DVB region, except the works in Refs. 35,38,40, where the oscillation frequency was found to increase first and then decrease with increasing voltage. In the present work, we investigate the voltage dependence of the current oscillation period in the DVB region in a microscopic resonant tunneling model.…”
Section: Introductionmentioning
confidence: 98%
“…2 agrees well with the results reported in previous works. 35,38 Here, we observe two new phenomena: (1) A new period branch (branch number 0) appears at the left side of the DVB region. (2) It is shown that the U-shaped period curve is divided into many discrete branches.…”
Section: Discrete Period Branchesmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, negative differential conductance can appear [Esaki & Tsu, 1970] (see Fig.1(b)). Thus, semiconductor superlattices can be used as generators of current oscillations, whose frequency depends on the parameters of the superlattice structure and the applied voltage, and thus, can be varied in a wide range from some hundred kHz [Cadiou et al, 1994;Hofbeck et al, 1996;Kastrup et al, 1995;Wang et al, 2000] to hundreds of GHz [Schomburg et al, 1999], which makes this system very promising for practical applications. On the other hand, the inherent nonlinearity gives rise to complex spatio-temporal dynamics of the charge density and the field distribution within the device, including the formation of travelling charge accumulation and depletion fronts and field domains associated with current oscillations.…”
Section: Introductionmentioning
confidence: 99%